Interasionisme Simbolik Novel al-Qanfadz Karya Islam Abu Syakir - Budiman, Arief (Al-Fashahah: Journal of Arabic Education, Linguistics, and Literature, 2021)
This article aims to reveal the reasons for the action of the main character in the novel and the existing meaning of the novel. By utilizing Gerard Mead's symbolic interactionism theory, this research fosters the stages experienced by the main character into four stages namely impulse, perception, manipulation, and consumption. After the phases experienced by the main character are known, followed by interactions experienced by the main character with other characters and concepts circulating in his mind. The result of this reading is that the main motive of the main character in carrying out the killings is to protect his power. The killings were carried out because the character 'I' considered death a pleasure and victory, because he had experience with killing hedgehogs who attacked from behind when feeling threatened. The meaning of this novel is that the writer wants to convey that the current Syrian leader in the eyes of the writer is nothing more than someone who has the desire to kill as a pleasure with the ultimate goal of victory.Keyword: al qanfadz novel, Islam Abu Syakir, symbolic interactionism, Arabic literature, Mead